Inclusion of viologen cations leads to switchable metal–organic frameworks. (26th October 2020) - Cadman, Laura K.; Mahon, Mary F.; Burrows, Andrew D.
Abstract : A series of anionic zinc-based MOFs have been prepared and electron transfer reactions involving the viologen counter-cations studied. Abstract : The reactions of Zn(NO3 )2 ·6H2 O with the polycarboxylic acids 1, 3-benzenedicarboxylic acid (H2 mbdc), 1, 4-benzenedicarboxylic acid (H2 bdc), 1, 3, 5-benzenetricarboxylic acid (H3 btc) and 4, 4′-biphenyldicarboxylic acid (H2 bpdc) in the presence of methyl viologen iodide ([MV]I2 ) in DMF gave anionic frameworks with methyl viologen species incorporated as counter-ions. When the reactions were carried out at 120 °C, the blue products [MV][Zn3 (mbdc)4 ] (1-ht ), [MV]0.44 [H2 MV]0.36 [NMe2 H2 ]0.4 [Zn3 (bdc)4 ]·0.6DMF (2-ht ), [MV]0.5 [Zn(btc)]·DMF (4-ht ) and [MV][Zn4 (bpdc)5 ]·8DMF·10H2 O (5-ht ) were formed, and these were shown to contain the radical cation [MV]˙ + . In contrast, the same reactions carried out at 85 °C gave orange isostructural compounds containing the dication [MV] 2+ . Similar observations were made for reactions with ethyl viologen bromide. The compounds 1-ht, 2-ht and 4-ht contain similar framework topologies to analogues in which NMe2 H2 + is the included cation. In contrast, 5-ht is based on a previously unreported interpenetrated network. Compound 2-ht contains the protonated species [H2 MV] 2+ in addition to [MV]˙ + and the crystal structure shows that the two rings in the former are staggered with respect to each other. This species is believed to form under the reaction conditions employed in the synthesis and the formation of [H2 MV] 2+ is suppressed by using an alternative approach in which methyl viologen is formed in situ from viologen diacetic acid. In the bdc-containing products, the radical cation is rapidly oxidised to the dication on exposure to air, as witnessed by the colour change from blue to orange. This change is reversed either by heating to 120 °C or exposure to UV radiation, both under nitrogen. This is in contrast to observations with the mbdc and btc analogues 1-ht and 4-ht, as in these compounds the blue colour persists for weeks. The difference can be related to the structures, with the channels present in 2-ht allowing oxygen to reach the radical cations.